Методика формування управлінської звітності підприємства - Ясінська, А. І.; Демків, Н. І.; Yasinska, A. I.; Demkiv, N. I. (Видавництво Львівської політехніки, 2017)
У статті розглянуто поняття управлінської звітності підприємства, основні вимоги щодо формування в ній інформації, розглянуто класифікацію та види управлінської звітності, яка досліджена науковцями, а також основні етапи побудови методології управлінської звітності.

The article analyzes approaches towards interpreting of the tem «managerial accounting» in papers of different scientists, provides key information groups, namely strategic, tactical and operative. It has been established that confidentiality is an important characteristics of information which encompasses all the three groups. In order to achieve the desired result and make efficient managerial decisions it is necessary to consider the main stages of decision-making process which is why scientists set out certain criteria for creating managerial accounting and the main requirements as to information which must factor in the forms, purpose, structure and users of a certain type of managerial accounting. In view of the unique character of managerial accounting system at each particular enterprise, classification and types of managerial accounting in the papers of scientists testify to absence of a single approach. Authors use different criteria and attribute different types of managerial accounting to them. The article summarizes approaches towards classification, lays out the principal, in our opinion, features and types of accounting which may be attributed to them. Owing to organizational specificities of enterprise operation, introduction of methods of managerial accounting must be done in a systemic manner. A systemic approach will help develop a model for processing, interpretation and transfer of information on different managerial levels, both for formation managerial accounting and making managerial decisions, and clearly determine its purpose, certain criteria, tasks, trends, requirement and approaches. Apart from that, the article lays out certain stages of structuring for determining a specific methodology of managerial accounting formation which include: determining of the main aim and setting objectives for managerial accounting; determining the content, structure, form and terms for submitting managerial accounting; determining the link between structure of financial, tax, statistical and other accounting indices and the structure of additional indices of managerial accounting; determining and reflecting efficiency indices in managerial accounting; control and analysis of managerial accounting enforcement.
Methods of creating managerial accounting at enterprise
Keywords: управлінська звітність; класифікація; види управлінської звітності; вимоги щодо інформації; методика формування; managerial accounting; classification; types of managerial accounting; requirements for information; methods of formation; 657. 37